Mast cell MrgprB2 in neuroimmune interaction in IgE-mediated airway inflammation and its modulation by β-arrestin2 - Sutradhar, Sangita; Ali, Hydar (Frontiers in Immunology, 2024)
Allergic asthma has been linked to activation of mast cells (MCs) by the neuropeptide substance P (SP), but the mechanism underlying this neuroimmune interaction is unknown. Substance P produced from cutaneous nociceptors activates MCs via Mas-related G-protein-coupled receptor B2 (MrgprB2) to enhance type 2 immune response in experimental atopic dermatitis in mice. We recently showed that the adapter protein β-arrestin2 (β-arr2) contributes to MrgprB2-mediated MC chemotaxis. The goals of this study were to determine if MrgprB2 facilitates neuroimmune interaction in IgE (FcRI)-mediated allergic airway inflammation (AAI) and to assess if this response is modulated by β-arr2. Wild-type (WT), MrgprB2 -/-mice and mice with MC-specific deletion of β-arr2 (Cpa3 Cre+ /β-arr2 fl/fl ) were passively sensitized with anti-TNP-IgE and challenged with antigen. The generation of SP and MC recruitment in the lung were determined by immunofluorescence and toluidine blue staining, respectively. The transcripts for Tac1, MrgprB2, TNFα and Th2 cytokines in lung tissue were assessed by RT-PCR and the release of selected cytokines in bronchoalveolar lavage (BAL) were determined by ELISA. Eosinophil and neutrophil recruitment in lung tissue and BAL were determined by immunofluorescence staining and flow cytometry, respectively. Goblet cell hyperplasia was determined by Periodic acid Schiff staining. Following IgE sensitization and antigen challenge in WT mice, SP generation, MC recruitment, transcripts for Tac1, MrgprB2, TNFα and Th2 cytokine were upregulated when compared to control challenge. TNFα, Th2 cytokine production, eosinophil/neutrophil recruitment and goblet cell hyperplasia were also increased. These responses were significantly reduced in MrgprB2 -/-and Cpa3 Cre+ /β-arr2 fl/fl mice. The data presented herein suggests that SP-mediated MrgprB2 activation contributes to AAI and goblet cell hyperplasia in mice. Furthermore, these responses are modulated by β-arr2, which promotes MC recruitment to facilitate their activation through FcRI.